Missed opportunities for prevention of mother -to-child transmission of HIV (PMTCT) in Ibadan, Southwest Nigeria (2014)
Background: Nigeria has the largest paediatric HIV-infected population in the world. Missed opportunities for prevention of mother-to-child transmission of HIV (PMTCT) compromise efforts at eliminating new pediatric HIV infections. Methods: Six hundred children, aged < 15 years, presenting to the pediatric units of the University College Hospital (UCH), Ibadan Southwest Nigeria between June to December 2007 were studied. The demographics, HIV status and socioeconomic status of mothers and their children were studied. A 4-step hierarchy was used to assess the missed opportunities for PMTCT. Step 1: utilization of a health facility for antenatal care and delivery; Step 2: maternal HIV status determination during pregnancy; Step 3: provision of antiretroviral medication to HIV-infected mother and baby; and Step 4: avoidance of mixed feeding in HIV-exposed children. The rates of missed opportunities for PMTCT services at different steps in the PMTCT cascade, perinatal transmission rates, and associated factors were reported. Results: There were 599 mothers and 600 children (one set of twins), 60 (10%) were HIV infected and 56 (93.3%) of these were adjudged perinatally infected. Of 78 HIV-infected women, 7 (9.0%) accessed all interventions in the PMTCT cascade and 71 (91.0%) had missed opportunities for PMTCT. Missed opportunities for PMTCT occurred 42.9% in cascade Step 1, 64.2% in Step 2, 52.6% in step 3 and 73.7% in Step 4. All mother-baby pairs who accessed complete PMTCT interventions received care at a teaching hospital. Among infants with perinatal HIV infection, 53 (94.6%) were born to mothers who had missed opportunities for PMTCT. Most women with missed opportunities attended antenatal care outside the teaching hospital setting and belonged to low socioeconomic status. Conclusion: It is imperative to expand PMTCT access to women who receive antenatal care outside the teaching hospitals and to those of low socioeconomic status.